Graphisches Kabinett : Fall 1987. - Kunsthandel Wolfgang Werner KG, Bremen; Helen Serger, la boetie, inc., New York (New York : Helen Serger/La Boetie Inc., 1987)
Modersohn-Becker, Paula ; Pechstein, Max ; Nolde, Emil ; Rohlfs, Christian ; Schiele, Egon ; Davidovich Burliuk, Vladimir ; Kandinsky, Wassily ; Léger, Fernand ; Schwitters, Kurt ; Klee, Paul ; Miro, Joan ; Ernst, Max
Graphisches Kabinett, Kunsthandel Wolfgang Werner KG, Bremen / Helen Serger/La Boetie, Inc., New York, 1987
boek